2008
DOI: 10.1016/j.vaccine.2008.03.040
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of mumps in Italy

Abstract: a b s t r a c tIn Italy, although vaccination has been recommended for a number of years, vaccination coverage for mumps is still sub-optimal. The objective of the present study was to evaluate the seroprevalence of mumps antibodies in the Italian population, stratified by age, gender and geographical area. The proportion of individuals positive for mumps antibodies remained stable in the age classes 0-11 months and 1 year (25.4% and 30.8%, respectively) and showed a continuous increase after the second year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…14,18 The overall seroprevalence values for young adults are similar to those obtained in studies from Madrid, Catalonia, and other surrounding countries. 15,20,25,26 was reflected in these studies, the peak seroprevalence in this age group could be indicative of a recent B. pertussis reinfection, thereby allowing this population to become an important potential reservoir and transmit the disease to children.…”
Section: Resultsmentioning
confidence: 71%
“…14,18 The overall seroprevalence values for young adults are similar to those obtained in studies from Madrid, Catalonia, and other surrounding countries. 15,20,25,26 was reflected in these studies, the peak seroprevalence in this age group could be indicative of a recent B. pertussis reinfection, thereby allowing this population to become an important potential reservoir and transmit the disease to children.…”
Section: Resultsmentioning
confidence: 71%
“…TB vaccination is mandatory for HCWs at a high risk of getting the disease [21]. Little attention is given by HCWs to vaccination against measles, mumps and rubella, as well as against varicella, while these are fundamental for susceptible HCW since in recent years the epidemiology of these diseases has changed, involving more and more adults and older people instead of children [22,23,24,25]. The vaccination rate against pertussis is also low among HCWs, as a recent review demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, information about remaining and potentially accumulating susceptibility within the population is highly important to adjust preventive policy. Serum surveys provide a reliable source of data to estimate the current risk of infection across age groups, and to predict evolutions in the future [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%